English-Indonesian Subtitling Strategies Used in Paterson Movie - Widyaningsih, Putri; Tri Ediwan, I Nyoman; Sri Rahayuni, Ni Ketut (Udayana Journal of Social Sciences and Humanities; Vol 6 No 2 (2022): UJoSSH, September 2022DO - 10.24843/UJoSSH.2022.v06.i02.p02, 2022)
The purpose of this study was to identify and analyze the subtitling strategies based on Gottlieb (1992) translation theory and the translation accuracy according to translation theory by Larson (1998: 530) in the Paterson movie. This study used descriptive-qualitative method to analyze the data and documentation method applied to collect the data. Based on the results of the study, it can be concluded that there were 389 data found in Paterson movie with transfer (129 data), paraphrase (93 data), deletion (59 data), condensation (55 data), imitation (21 data), Expansion (17 data), decimation (14 data), and resignation (1 data). However, there were no transcription and dislocation strategies that had found in the Paterson subtitle translation. Meanwhile, for the translation accuracy, the findings show there were 281 out of 389 data that the translator translated it accurately, and 108 out of 389 data inaccurate translation. Therefore, the Indonesian subtitle of "Paterson" movie was categorized as an accurate translation text.